Três pontos de vista sobre cônicas - Oliveira Júnior, José William de (2018)
In the present work, we tried to investigate the conics in the synthetic, analytical and projective contexts, as well as to know some applications and properties of these curves. In the synthetic approach, it was emphasized a lithe of the historical aspects, the works made by Apollonius and Dandelin, a characterization for tangent and normal lines and re ecting properties. In the analytical approach, the Cartesian, polar and parametric equations were described, as well as the applications in the Kepler Laws. In the projective approach, the concepts of projective plane, projective point, projective line and projective applications were used to give meaning to the conic in the projective universe, in addition the Theorews of Pascal and Brianchon were demonstrated.